PENGUATAN PENGETAHUAN BENCANA GEMPA BUMI PADA MAHASISWA KESEHATAN MASYARAKAT UNIVERSITAS ESA UNGGUL TAHUN 2026 - Yusvita, Fierdania; Muda, Cut Alia Keumala; Utami, Desyawati; Andani, Dhea Julia (Jurnal Pengabdian Masyarakat AbdiMas, 2026)
AbstractAn earthquake is a series of events that can cause ground vibrations or shaking of the earth due to collisions and faults between plates. This community service activity aims to increase knowledge of earthquake disasters about the importance of natural disasters, especially in preventing and managing earthquake disasters. The counseling was carried out using interactive lecture and discussion methods, in November 2025 given by students and public health lecturers who explained the definition of earthquakes, their causes, and control. In the interactive discussion session, students could ask questions and share their experiences about earthquakes, this helped students in strengthening their understanding. This counseling was held at the Esa Unggul University Bekasi Campus and was attended by 122 students. The counseling activity began with the arrival of students, conducting health screenings, morning exercises and counseling which also included the distribution of pre-tests, delivery of materials, question and answer sessions, awarding prizes, handing over leaflets and posters and distributing post-tests. The counseling activity ran smoothly and conducively, marked by the active participation of participants throughout the activity. This can be seen through the results of the pre- and post-tests given to respondents, indicating an increase in knowledge regarding the earthquake disaster that had been presented.Keywords : Earthquake, Knowledge, and Students